Cost and Return of Nile Tilapia : Case Study of Ban Mabkrad, Khok Krachai Sub-District, Khon Buri District, Nakhon Ratchasima Province - Adsawatithisakul, Nalinee; Boonsuk, Kingkeaw; Keeratiu-rai, Nichada (NEU ACADEMIC AND RESEARCH JOURNAL, 2023)
The main purpose of the research was to study the costs and returns of Tilapia farming in the Cage at Ban map Krat, Khok Krachai sub-district, Khonburi district, Nakhon Ratchasima province. The sampling group was 16 fish farmers with at least 5-year experience who were registered with The Department of Fisheries. The data was collected by In-depth interviews and analyzed to find out the costs and returns. The results revealed that majority of responders were females (56.25%) between the ages of 41-50 (43.47%) with elementary education level (56.25%). and, the main occupation was Tilapia cage-farming (62.50%) with an average earning of 77,938 baht/cage. The total cost was 67,564.67 baht/cage including the variable cost was 64,916.67 baht/cage (96.08%) and the fixed cost was 2,648 baht/cage (3.92%). The net profit was 10,373.33 baht/cage, the profit margin was 13.31 % and the break-even point was 294.88 kg./cage.